To the Problem of Socio-Economic Views of Viacheslav Lypyns’kyj - Жидков, Сергій (V. N. Karazin Kharkiv National University Bulletin History of Ukraine. Ukrainian Studies: Historical and Philosophical Sciences, 2018)
The paper is devoted to the study of socio-economic views of Viacheslav Lypyns’kyj. The author, analyzing the creativity of historiosopher, traces the influences of various «hypostases»/identities of the intellectual on the formation of his socio-economic concepts. The understanding of the system «state-economic», capitalism and socio-economic differentiation by Viacheslav Lypyns’kyj is studied. The significance of the question about private ownership of land in the historiography of scholar is clarified. The basic postulates of agrarianism and «the farmer (khliborob) ideology» are compared. The «class discourse» in the texts of thinker and his «answer» to the «Marxist monopoly» in intellectual environment of epoch are highlighted.